A Y-shape connection device for pediatric patients with an indwelling catheter (Dia = 8Fr) during urodynamic studies, especially for filling phase measurements: a single-center prospective study for safety and effectiveness - Yang, Shi-Qin; Zeng, Xiao; Peng, Liao; Shen, Si-Hong; Zhang, Jie; Huang, Zhi-Hui; Shen, Hong; Luo, De-yi; Jin, Tao (Frontiers in Pediatrics, 2023)
This prospective study aimed to assess the effectiveness of a Y-shape connection device in reducing pain and bleeding in pediatric patients with indwelling catheters during urodynamic studies (UDS), while also obtaining effective results in the filling phase. A total of 45 pediatric patients with a mean age of 13 years were included, all of whom underwent both a UDS with the Y-shape connection device (Method A) and a standard UDS procedure (Method B). The Y-shape connection device demonstrated similar overall urodynamic parameters compared to the standard procedure, while also resulting in significantly less bleeding (P=0.006) and lower VAS scores during (1.12±0.58 vs. 3.88±1.01, P=0.001) and after (0.12±0.08 vs 2.91±0.89, P=0.001) the procedure. No adverse events were reported at the 1-month follow-up. These findings suggest that the Y-shape connection device can effectively reduce pain and bleeding during and after UDS in pediatric patients with indwelling catheters (Dia=8Fr), while also obtaining effective results in the filling phase. Therefore, this Y-shape connection device has a more significant value for children who require urodynamic studies and place more emphasis on filling phase parameters, especially for children with neurogenic bladder.